Las transiciones como historia global: una perspectiva desde América Latina - Riojas, Carlos (Revista Venezolana de Análisis de Coyuntura, 2014)
1989 es recordado por la caída del socialismo. Pero también es posible registrar hechos enAmérica Latina susceptibles de compararse con los cambios en Europa Central y contribuir en lareconstrucción de una historia global. El objetivo es analizar cuáles eventos en América Latinase enmarcan en el proceso de transformación en torno a 1989. El texto se divide en cuatro partes,primero se presenta una panorámica general en América Latina; en las siguientes tres seccionesse exponen los casos de Argentina, Chile y México y, por último, se propone fortalecer eldiálogo entre ambos subcontinentes mediante una agenda de investigación. Abstract Transitions as global history: A Latin American perspective We remember 1989 mostly as the year when the socialism of soviet type collapsed. However, there were also many equally important events in Latin America that we could compare with the principal transformation occurred in Central Europe this year in order to e in the reconstruction of a Global History. The aim of this paper is to analyze what kind of facts in Latin America could be framed as part of the transformation processes around 1989. The text is divided into four parts. First, we present a general overview in Latin America during the eighteens. In the following three sections we expose the cases of Argentina, Chile and Mexico. Finally, we propose to strengthen the dialogue between the two sub-continents through a research agenda in this comparative vein.